2017
DOI: 10.2118/180703-pa
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Based Casing Design for Cyclic-Steam-Stimulation Wells

Abstract: Summary An oil field in Xinjiang, China, experienced a casing failure rate of 15 to 30% in thermal wells, mainly relating to inadequate protocols of casing design. This paper presents a new strain-based casing-design method. New material parameters are proposed to build safety-evaluation principles throughout the service life of a thermal well. In addition, a gas-tight thread joint is applied to prevent steam leakage that otherwise would cause a large transversal stress between different formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The casing deformation of shale gas wells in Sichuan area is largely controlled by formation movement, which results in local stress and strain concentration on the casing. This is significantly different from the casing failure of thermal wells because the latter belongs to overall and nearly uniform plastic deformation along the longitudinal direction throughout the whole casing string due to large temperature changes in wellbore [11]. Moreover, the slip of shale formation belongs to random distribution, which is significantly related to well trajectory, fracturing technology and geological migration, and so no one can exactly predict the failure location because of the complexity and randomness of the downhole factors.…”
Section: Status Of Strain Based Casing Designmentioning
confidence: 95%
“…The casing deformation of shale gas wells in Sichuan area is largely controlled by formation movement, which results in local stress and strain concentration on the casing. This is significantly different from the casing failure of thermal wells because the latter belongs to overall and nearly uniform plastic deformation along the longitudinal direction throughout the whole casing string due to large temperature changes in wellbore [11]. Moreover, the slip of shale formation belongs to random distribution, which is significantly related to well trajectory, fracturing technology and geological migration, and so no one can exactly predict the failure location because of the complexity and randomness of the downhole factors.…”
Section: Status Of Strain Based Casing Designmentioning
confidence: 95%
“…The brittle shale formation possesses abundant beddings and fractures, and the shear slip in hydraulic fractures formed during the process of high parameter hydraulic fracturing technology. The shear slip at different positions of fractures is calculated based on given fracture length, angle, friction coefficient and rock mechanics parameters of shale formation [10][11].…”
Section: Formation Slip Induced By High-parameter Hydraulic Fracturin...mentioning
confidence: 99%
“…However, significant elongation may occur leading casing failure in tension or compression if design do not integrate local loads Yamada et al (2018). Han et al (2018) examined strain-based casing design for cyclic steam stimulation in an oil filed in China and reported 15-30% failure rate. The study concluded that the failure is mainly as a result of extra plastic deformation under tension and compression during thermal cycles.…”
Section: Deformation Regionmentioning
confidence: 99%
“…This is attributed to the geological anomaly of a major fault that traverse across the carbonate oil-field (Asmari 'M') and casing age. In China, 15-30% casing failure in thermal recovery wells were due to substandard casing design according to Han et al (2018). The cyclic steam stimulation (CCS) process in this field adopt three different processes; which are steam injection, soaking and oil production.…”
Section: Introductionmentioning
confidence: 99%